Magnesium Deficiency: What Is Our Status?. Issue 3 (May 2016) - Hruby, Adela; McKeown, Nicola M.
Abstract : Low magnesium intake has been implicated in a broad range of cardiometabolic conditions, including diabetes, hypertension, and cardiovascular disease. Dietary magnesium and total body magnesium status are widely used but imperfect biomarkers in serum magnesium. Despite serum magnesium's limitations, it is nevertheless observed to be lower in those with cardiometabolic disease than in generally healthy people. Although some 50% of Americans do not meet recommended levels of magnesium intake, the extent of prevalent magnesium deficiency is unknown. Given magnesium's role in a multitude of chronic conditions that are increasingly common across the globe, here, we summarize recently published literature reporting prevalent hypomagnesaemia in generally representative populations and in populations with type 2 diabetes mellitus, metabolic syndrome, and obesity. On the basis of these studies, we estimate that up to a third of the general population may be magnesium deficient and that outside of acute clinical encounters or hospitalization, hypomagnesaemia is likely frequently overlooked in general clinical practice.